2021
DOI: 10.3390/su13116023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Altruistic Motives on Organic Food Purchase: Theory of Planned Behavior

Abstract: Marketing campaigns of organic food emphasize utilitarian benefits and psychological benefits as well as consumer culture to enhance environmental sustainability. In order to study the purchase intention of organic food, the authors developed a model using antecedents like warm glow, subjective norm, attitude and perceived behavioral control. This study examines the model for the Indian and the USA samples and thus integrated using three theories: Theory of Planned Behavior (TPB), Pro-Social Behavior (PSB) The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 78 publications
1
25
0
1
Order By: Relevance
“…For example, Hartmann and Apaolaza-Ibanez [13] found that consumers who felt a warm glow when exposed to experimental green energy brands had a positive influence on their attitude toward the brand. According to Boobalan, Nachimuthu, and Sivakumaran [42], when consumers purchase organic foods, they feel a warm glow, which positively affects attitude. In addition, Bhutto et al [43] discovered that consumers who purchased energy-efficient home appliances felt warm glow benefits, resulting in positive effects on attitude toward the products.…”
Section: Psychological Benefits Of Using An Eco-friendly Tv Home Shop...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hartmann and Apaolaza-Ibanez [13] found that consumers who felt a warm glow when exposed to experimental green energy brands had a positive influence on their attitude toward the brand. According to Boobalan, Nachimuthu, and Sivakumaran [42], when consumers purchase organic foods, they feel a warm glow, which positively affects attitude. In addition, Bhutto et al [43] discovered that consumers who purchased energy-efficient home appliances felt warm glow benefits, resulting in positive effects on attitude toward the products.…”
Section: Psychological Benefits Of Using An Eco-friendly Tv Home Shop...mentioning
confidence: 99%
“…In anticipating consumer behavior, the TPB is a more appropriate model because the TRA only considers volitional factors, whereas the TPB also includes behavior determined by nonvolitional factors, such as resources [48]. Although the TPB was proposed more than three decades ago, numerous researchers have been proving this framework in consumer behavior until recently (e.g., [42,49,50]). For instance, Boobalan et al [42] applied the TPB model successfully to investigate the motivations for consumers to purchase organic foods.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of planned behaviour (TPB) [17,18] is a well-known and supported framework to explain and predict the consumption of organic food [19][20][21][22][23]. Several previous studies have indicated that the three core components of human behaviour proposed by the TPB framework, namely, attitude [24][25][26], subjective norms [24,[27][28][29], and perceived behavioural control [30,31], altogether lead to the formation of organic food purchasing intention.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
“…The marketers contemplate on attitudinal issues, they desire to deal organically created food products to developed civilization Boobalan et al (2021). The Consumers understand green products as a further in luential changeable to in luence green product business decisions.…”
Section: Personal Experience Of Usage Of Green Productsmentioning
confidence: 99%